Self-assessment System: Detrimental Effects on Entrepreneurial and Innovative Activity - Kovač, Mitja; Kotnik, Patricia (LeXonomica, 2015)
<span style="font-family: ’Times New Roman’,serif; font-size: 12pt; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-style: italic; mso-bidi-font-size: 10.0pt; mso-bidi-language: AR-SA;" lang="EN-GB">Efficient regulatory mechanisms that induce innovation, co-operation and deter competition law infringements have recently been the subject of growing attention. <span style="font-family: ’Times New Roman’,serif; font-size: 12pt; mso-ansi-language: EN-GB; mso-fareast-language: SL; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-style: italic; mso-bidi-font-size: 10.0pt; mso-bidi-language: AR-SA;" lang="EN-GB">C<span style="font-family: ’Times New Roman’,serif; font-size: 12pt; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-style: italic; mso-bidi-font-size: 10.0pt; mso-bidi-language: AR-SA;" lang="EN-GB">ompetition is essential to the innovation process which in general terms enables entrepreneurship. But so too is co-operation between firms which requires an exchange of information and may lead to inefficient collusive behaviour. The optimal trade-off between the provision of stable entrepreneurial incentives and the new European competition law’s reform with the self-assessment system has been largely missing from the current scholarly debate. This paper identifies the unintended, harmful horizontal side effects of this new European self-assessment system upon the entrepreneurial activity, offers a legal evaluation of the optimal entrepreneurial incentive mechanisms and provides legal and entrepreneurial arguments for an improved regulatory response.